Combinatorial immunotherapy strategies for hepatocellular carcinoma. (April 2016) - Tagliamonte, Maria; Petrizzo, Annacarmen; Tornesello, Maria Lina; Ciliberto, Gennaro; Buonaguro, Franco M; Buonaguro, Luigi
Highlights: Current treatments for liver cancer have poor efficacy. Few immunotherapy strategies have been tested with unsatisfactory results. The liver microenvironment is highly immunosuppressive and needs to be contrasted. Specific target antigens are needed for developing effective therapeutic vaccines. Combinatorial strategies will likely result in improved results. Abstract : Hepatocellular carcinoma (HCC) is the most common liver malignancy. The prognosis for HCC patients greatly varies according to the stage at diagnosis. Overall it is poor, with a 5-year survival rate of approximately 5–6%. Immunotherapeutic interventions represent a novel and effective therapeutic tool. However, only few immunotherapy trials for HCC have been conducted so far with contrasting results, suggesting that significant improvements are needed. Indeed, the liver is characterized by a strong intrinsic immune suppressive microenvironment which needs to be counterbalanced with immune stimulatory approaches. Therefore, the implementation of combinatorial protocols combining immune stimulatory strategies with specific immunotherapy approaches could result in a dramatic improvement of efficacy and clinical outcome in HCC patients. The present review aims at describing the state of the art in immunotherapy strategies for HCC and future perspectives.